2016
DOI: 10.1007/s00705-016-2866-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of respiratory viral infections in children in Shanghai, China

Abstract: Acute respiratory tract infections (ARTIs) due to various viruses are not only the most common causes of upper and lower respiratory infection but are also major causes of morbidity and mortality in children. In this study, we investigated the prevalence and clinical characteristics of children with virus-related ARTIs and determined the spectrum of respiratory viruses and their correlation with meteorological variables in Jiading District, Shanghai, China. Nasopharyngeal swabs from 2819 children with ARTIs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 23 publications
5
32
2
1
Order By: Relevance
“…Our study is the first to compare respiratory viral infections and their epidemiology in hospitalized children with SARI in Beijing and Shanghai. Of the 700 patients included in the study, 78.1% tested positive for at least one virus; this rate was higher than that reported by previous studies (range, 34.6-70.3%) [18][19][20][21][22][23][24][25]. This finding may be mainly explained by some differences in the SARI case inclusion criteria, since additional criteria in our study were a normal or low leukocyte count or indrawing of the lower chest wall.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Our study is the first to compare respiratory viral infections and their epidemiology in hospitalized children with SARI in Beijing and Shanghai. Of the 700 patients included in the study, 78.1% tested positive for at least one virus; this rate was higher than that reported by previous studies (range, 34.6-70.3%) [18][19][20][21][22][23][24][25]. This finding may be mainly explained by some differences in the SARI case inclusion criteria, since additional criteria in our study were a normal or low leukocyte count or indrawing of the lower chest wall.…”
Section: Discussioncontrasting
confidence: 63%
“…Either the total or age groupmatched positive rates of RSV, HCoV, and HMPV significantly differed in Beijing and Shanghai (P < 0.05). In addition, a comparison of our data with those from other studies collected during the same period in the same locations revealed that our infection rates differed from those of the other studies [15,19,25]. Differences in detection methods and primers, sample collection, and subject populations may account for this disparity.…”
Section: Discussioncontrasting
confidence: 62%
“…Respiratory virus infections are a major public health problem, due to the ease of spread and considerable morbidity and mortality. The association between respiratory tract infections and different viral pathogens has been reported to vary between 40% and 90% [1][2][3][4][5] globally.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the performance of the novel assay, 40 nasopharyngeal swabs collected from children with ARTIs in our previous studies were used [29,30]. Among these samples, half were previously detected as RSV-positive and half as RSV-negative using our in-house multiplex RT-qPCR method.…”
Section: Methodsmentioning
confidence: 99%